Assessing awareness on biodiversity conservation among Nigerians: the Aichi Biodiversity Target 1 (2021)
The adoption of the Aichi Biodiversity Targets (ABTs) was supposed to increase conserva tion awareness in diferent countries and regions of the world. However, there seems to be a limited understanding of the importance of ecosystem services, ofered by biological diver sity. Thus, the continued decline in biodiversity, especially in developing countries. This study appraised the level of success of the frst target of Nigeria’s National Biodiversity Strategy and Action Plan (NBSAP), which is hinged on the frst ABT. In a national survey, data were obtained from a total of 1,124 respondents (839 professionals and 285 non-pro fessionals), using a structured questionnaire. Information on the respondents’ knowledge of biodiversity conservation and the associated ecosystem services, were elicited. Most of the non-professionals had a low level of understanding of biodiversity concepts (4.9±1.7 to 20.5±3.4%), while there was a moderate level of understanding among the professionals (48.0±8.6 to 88.8±3.4%). Awareness of the NBSAP was low for both groups (43.8±7.2% professionals and 12.1±3.7% non-professionals). The study concludes that there is a need to step up campaigns on biodiversity conservation in Nigeria and promote visits to natural sites. Youth engagement through the employment of graduates of biology-related disci plines, to educate the public on biodiversity conservation and the action plan, could also be a strong determinant to the success of the NBSAP targets.